Hypomagnesaemia in Acute Exacerbation Chronic Obstructive Airway Disease; Association with Anthonisen’s Levels of Exacerbation - Javaira Aziz, Muhammad Amir, Abrar Akbar, Sadia Aziz, Nadia Shams, Lubna Meraj, Javaira Aziz, Muhammad Amir, Abrar Akbar, Sadia Aziz, Nadia Shams, Lubna Meraj (Journal of Rawalpindi Medical College, 2022)
Background: COPD is major public health issue causing morbidity and mortality. Lower serum magnesium levels are seen in patients with acute exacerbations compared to stable COPD patients. This study aims at identifying hypomagnesemia as predictor of COPD exacerbations that may help reduce the burden of readmissions and mortality. Material and Methods: The Descriptive cross-sectional study was conducted –removed for blind review—from 16 July 2016 to 15 Jan 2017 after the ethical approval and informed consent. The indoor adult (>18years) diagnosed cases of COPD exacerbation were included by consecutive sampling. Patients with malignancy, pregnancy and receiving magnesium supplements were excluded. Demographic details documented and after complete clinical evaluation, serum Magnesium levels of were assessed. Serum Magnesium < 1.80 mg/dl labeled hypomagnesaemia. Data was analyzed by SPSS with significant p< 0.05. Results: Amongst 176 patients; there were 93(52.8%) males and 83(47.2%) females. Mean age was 56+7 years. Mean duration of COPD was 6.56 + 5.24 years (2-10 years). Mean height in the study was 181 +12 cm and mean weight was 56.06 + 7.08 kg. The mean serum magnesium level was 1.5 + .49mg/dl. Low serum magnesium (<1.8 mg/dl) observed in 103(58.5%), gender wasn’t associated with hypomagnesaemia (p=0.294). Hypomagnesaemia in accordance to types of Anthonisen’s criteria was observed in 19(44.2%) with Type I, 37(57.8%) with Type II and 47(68.1%) with Type III COPD exacerbation. Hypomagnesaemia had significant association with Anthinosen’s levels of exacerbation (p=0.043). The mean age in patients with hypomagnesaemia was 56.61+6.78 Vs. 55.30+7.47 in patients without hypomagnesaemia (p=0.228). Conclusion: The study concludes mean serum magnesium levels are significantly lower in patients with acute exacerbation of COPD (58.5%), particularly in type II and III. Magnesium levels should be performed in all COPD exacerbations irrespective of gender and age. Replacement of magnesium may be helpful in alleviating symptoms and reducing frequency of exacerbations. KEYWORDS: COPD. Acute exacerbation. Serum Magnesium levels. Hypomagnesaemia.